Penerapan Portofolio Digital sebagai Media Evaluasi dan Refleksi dalam Penguatan Profil Pelajar Pancasila - Nasir, Rahma; Pathuddin; Anggraini; Sugita, Gandung (Rengganis Jurnal Pengabdian Masyarakat, 2025)
This community service program aims to introduce digital portfolios using Google Sites at SMPN 12 Palu in support of the Strengthening Pancasila Student Profile (P5) program. Digital portfolios have become an essential tool in modern education, serving as a means of documentation, reflection, and evaluation. Additionally, digital portfolios allow students to systematically compile their learning records, making it easier to monitor their academic progress and skill development. The methods used in this program include training, mentoring, and participatory evaluation involving students and teachers to ensure the effective implementation of digital portfolios. The primary focus of this initiative is to strengthen digital skills that support inclusive and sustainable learning. In addition to enhancing digital literacy, this program also assists students and teachers in adopting educational technology more effectively. The results indicate that digital portfolio training successfully improved the digital competencies of both students and teachers, enabling greater transparency in the educational process. Furthermore, this implementation reinforces Pancasila values in learning, particularly through the development of students' character, creativity, and independence in exploring and presenting their learning outcomes.